2020
DOI: 10.1097/olq.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

Five Waves of an Online HIV Self-Test Giveaway in New York City, 2015 to 2018

Abstract: Publication of this report would not have been possible without the hard work and dedication of state and local health departments that collected and submitted the HIV test-level data. We also acknowledge the contributions of Lisa Belcher and Janet Heitgerd of the Program Evaluation Branch;Stephanie Thurman of CACI International, Inc.; the Quantitative Sciences and Data Management Branch; and the Prevention Program Branch for their contribution toward monitoring and strengthening HIV prevention efforts in stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Frequent testers were easier to recruit than infrequent or never testers, suggesting that routine testing may be more common among MSM in NYC than among the men in this study. To recruit never or infrequent testers, we relied on 16 referrals from a study evaluating the NYC Home Test Giveaway [ 47 ], including 10 men who reported that they had never had an HIV test before receiving their self-test kit. Home delivery of a free test kit was an intervention that only 16 men received, and could be viewed as a source of bias as it altered these men’s experience of HIV testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent testers were easier to recruit than infrequent or never testers, suggesting that routine testing may be more common among MSM in NYC than among the men in this study. To recruit never or infrequent testers, we relied on 16 referrals from a study evaluating the NYC Home Test Giveaway [ 47 ], including 10 men who reported that they had never had an HIV test before receiving their self-test kit. Home delivery of a free test kit was an intervention that only 16 men received, and could be viewed as a source of bias as it altered these men’s experience of HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited 71 participants through a variety of sources: 20 through Grindr, Jack’d, and Adam4Adam—online sex hook-up apps and websites used by MSM; 11 from the Craigslist.com volunteer opportunities board; 7 during in-person outreach in public places and events where MSM socialize; 6 at gay bars; 1 through passive distribution of recruitment cards at an NYC Sexual Health Clinic; and the rest through referrals, including from an NYC Health Department study evaluating the HIV Home Test Giveaway [ 47 ] (16), another study of HIV self-testing (3), an HIV prevention and care clinic (3), study personnel (3), and from other participants (1). With referrals from the NYC Health Department Home Test Giveaway, we sought out MSM who had never tested prior to their home test (10 of 16), again due to difficulty recruiting men who never tested or tested infrequently.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that significant barriers to HIV testing included stigma, confidentiality issues and inconvenience accessing a testing facility [ 38 , 39 ]. In Western countries, specific populations, such as MSM, tend to accept HIV self‐testing and have high testing rates through free online ordering or outreach services [ 15 , 16 , 17 ]. In Taiwan, the official estimate of the MSM population is approximately 1.7% of the adult male population [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in Asia, some countries, including Thailand and Vietnam, have started HIVST pilot programs or studies [ 7 , 8 , 9 ], but most countries remain in the pre‐implementation stage [ 10 , 11 , 12 , 13 , 14 ]. In Western countries, men who have sex with men (MSM) tend to utilize HIVST through free online ordering or outreach services [ 15 , 16 , 17 , 18 ]. However, these studies rarely measured the association between HIVST access and the trends of annual new HIV diagnosis at the population level.…”
Section: Introductionmentioning
confidence: 99%
“…Different diagnostic technologies in rapid diagnostic methods can help improve the diagnosis and ultimately control the disease. In March 2004, the HIV Antibody Rapid Detection Kit, introduced by the US Food and Drug Administration for salivary uid samples in all individuals, became the rst HIV Self-Test, or home testing [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%